2008
DOI: 10.1016/j.jconrel.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumoral effect of vinblastine and HSV-Tk/GCV gene therapy mediated by albumin-associated cationic liposomes

Abstract: Despite recent advances in conventional therapeutic approaches for cancer, the frequently observed acquired drug resistance and toxic side effects have limited their clinical application. The main goal of this work was to investigate the combined antitumoral effect of vinblastine with HSV-Tk/GCV "suicide" gene therapy mediated by human serum albumin (HSA)-associated lipoplexes, in mammary adenocarcinoma cells (TSA cells). Our results show that, among the different lipoplex formulations tested, HSA-associated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…15 Our results demonstrated that the incorporation of lactosyl-PE in the nanocarriers (EPOPC:Chol:lactosyl-PE/DNA) promoted a substantial increase in their biological activity in HepG2 cells (Figures 1 and 2). This enhancing effect was dependent on the amount of lactosyl-PE and on the (+/-) charge ratio of lipoplexes, the highest increase in biological activity being achieved for nanosystems containing 15% of lactosyl-PE and prepared at the 2/1 (+/-) charge ratio.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…15 Our results demonstrated that the incorporation of lactosyl-PE in the nanocarriers (EPOPC:Chol:lactosyl-PE/DNA) promoted a substantial increase in their biological activity in HepG2 cells (Figures 1 and 2). This enhancing effect was dependent on the amount of lactosyl-PE and on the (+/-) charge ratio of lipoplexes, the highest increase in biological activity being achieved for nanosystems containing 15% of lactosyl-PE and prepared at the 2/1 (+/-) charge ratio.…”
Section: Discussionmentioning
confidence: 55%
“…21,[24][25][26][27] On the other hand, we have previously shown that the use of cationic liposomes composed of EPOPC and Chol, at a 1:1 molar ratio, results in considerably higher biological activities than those obtained with other lipid-based formulations. [13][14][15][16][17]28 In this regard, the main goal of this work consisted of the development of a new gene delivery lipid-based nanosystem for HCC, targeting the ASGP-R, based on cationic liposomes composed of EPOPC, Chol and lactosyl-PE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations